Enfrentamento intersetorial da violência contra as mulheres: uma análise da Casa da Mulher Brasileira - Piasentini, Luisa Cassula (2022)
The present dissertation aims to study the Casa da Mulher Brasileira (“Brazilian Women's House”), as an institutional mechanism that favors intersectoriality in the fight against violence against women and, thus, seeks to contribute to the debates on the institutional dimension of confronting violence against women in Brazil. We start from the understanding of violence against women as a complex phenomenon, which requires the mobilization and integration of different fields of knowledge to enable the comprehensive care of women in situations of violence. This understanding was incorporated into the Brazilian legal system by Law nº 11.340/2006 (Maria da Penha Law), which emphasizes the creation and execution of integrated measures to prevent and repress violence, as well as assistance to women in situations of violence. Such integration, brought about by this new normative paradigm, constitutes an implementation challenge, with the Casa da Mulher Brasileira having emerged to deal directly with the issue of intersectoriality. The Casa da Mulher Brasileira constitutes the priority action of the Mulher Viver Sem Violência Program, a public policy of national scope, created in 2013, which integrates a larger set of policies aimed at the realization of women's rights promoted by the Federal Government. From the analysis of the institutional design of the Casa da Mulher Brasileira and its functioning, we discuss the strengths and weaknesses of the model, considering the implementation’s challenge of the full assistance in Brazil and international experiences with similar models.